2002
DOI: 10.1017/s1355838202025050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interactions among the Cef1p-Prp19p-associated splicing complex

Abstract: Schizosaccharomyces pombe (Sp) Cdc5p and its Saccharomyces cerevisiae (Sc)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
146
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(156 citation statements)
references
References 65 publications
6
146
0
Order By: Relevance
“…Cwc2 also comigrated with Prp19 and other core NTC proteins in the glycerol gradient (Table 2). However, it is only loosely associated with the NTC complex (Ohi and Gould 2002), which may explain the low precipitation efficiency of the U2 snRNP and IL RNA. Taken together, our immunoprecipitation results indicate that a part of the NTC complex remains associated with a fraction of the U2 and U5 snRNPs as well as the IL RNA after ILS dissociation by the NTR complex.…”
Section: Cold Spring Harbor Laboratory Press On March 24 2019 -Publimentioning
confidence: 99%
“…Cwc2 also comigrated with Prp19 and other core NTC proteins in the glycerol gradient (Table 2). However, it is only loosely associated with the NTC complex (Ohi and Gould 2002), which may explain the low precipitation efficiency of the U2 snRNP and IL RNA. Taken together, our immunoprecipitation results indicate that a part of the NTC complex remains associated with a fraction of the U2 and U5 snRNPs as well as the IL RNA after ILS dissociation by the NTR complex.…”
Section: Cold Spring Harbor Laboratory Press On March 24 2019 -Publimentioning
confidence: 99%
“…Based on epistasis analysis PSO4 was assigned to both the yeast RAD6 and RAD52 groups indicating the pleiotropic nature of this mutation [3,4]. Interestingly, cloning of PSO4 showed that it was allelic to PRP19 a previously characterized component of the pre-mRNA splicing complex in both yeast and human cells [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on epistasis analysis PSO4 was assigned to both the yeast RAD6 and RAD52 groups indicating the pleiotropic nature of this mutation [3,4]. Interestingly, cloning of PSO4 showed that it was allelic to PRP19 a previously characterized component of the pre-mRNA splicing complex in both yeast and human cells [5][6][7][8][9][10].The complete function of Prp19 in mRNA splicing is not known, however, it has been shown that the Prp19p-associated complex is required for activation of the pre-mRNA splicesome and for the stable association of the small nuclear RNAs U5 and U6 with the spliceosome after U4 is dissociated [11,12]. These findings suggest a possible structural role for the Prp19-associated complex in pre-mRNA splicing.…”
mentioning
confidence: 99%
“…In recent years, several complexes have been identified that seem to challenge previous models of spliceosome formation. These include the yeast Cwf/Cwc complex, 7,8 lnRNP complexes, 9 a complex larger than 150S with base paired U2 and U6, 10 a U2/U4/U5/U6-containing pseudospliceosome complex, 11 a pentasnRNP from S. cerevisiae, 12 and a HeLa nuclear extract penta-snRNP complex. 13 The exact functional relevance of these complexes remains to be determined, none have been shown to be capable of splicing on their own.…”
Section: Introductionmentioning
confidence: 99%